Interhemispheric approach to anterior communicating artery aneurysm: A case illustration - Senapati, Satya; Rathore, Lavlesh; Yamada, Yasuhiro; Kato, Yoko (Asian Journal of Neurosurgery, 2019)
There are two main types of approaches for anterior communicating artery (AcomA) aneurysms, namely pterional approach, and an interhemispheric (IH) approach. Pterional approach is the most common for anterior circulation aneurysms. However, this approach cannot be used without resection of gyrus rectus when aneurysm is located high within the IH fissure and directed posterosuperiorly, which is better handled with IH approach. In this article, we will describe the tricks of IH approach with a case illustration.
Keywords: Anterior communicating artery aneurysm; distal anterior cerebral artery aneurysm; interhemispheric approach